2022
DOI: 10.4174/astr.2022.102.2.90
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effect of biodegradable stents on biliary stricture and fibrosis after biliary anastomosis in a porcine model

Abstract: Purpose The current drain tubes for preventing surgically biliary anastomotic stricture are not naturally and easily removed. If a drain tube using biodegradable material is easily available and the degradation time of the tube is well controlled, surgical anastomotic stricture and fibrosis could be prevented. The aim of this animal study was to evaluate the preventive effect of novel biodegradable stents (BS) on biliary stricture and fibrosis after duct-to-duct (DD) biliary anastomosis. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…This result suggests that our 3D printed biodegradable biliary stent made of PCL is biocompatible, at least in the porcine model, and is highly unlikely to cause problems in humans. This is similar to the results of previous studies showing good biocompatibility of biliary stents made using PDO during 8- or 20-week follow-up periods in a porcine model 17 , 22 . Regarding human application, Mauri et al 10 demonstrated the safety and effectiveness of the PDO stents for benign biliary strictures with an over 80% patency rate after monitoring 107 cases for two years.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This result suggests that our 3D printed biodegradable biliary stent made of PCL is biocompatible, at least in the porcine model, and is highly unlikely to cause problems in humans. This is similar to the results of previous studies showing good biocompatibility of biliary stents made using PDO during 8- or 20-week follow-up periods in a porcine model 17 , 22 . Regarding human application, Mauri et al 10 demonstrated the safety and effectiveness of the PDO stents for benign biliary strictures with an over 80% patency rate after monitoring 107 cases for two years.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, fibrosis in the stent group was significantly thicker than that in the control group. According to another previous animal study using PDO biliary stents 22 , the degree of fibrosis in the control group was more marked than that in the stent group at the duct-to-duct biliary anastomosis site. However, in that previous study, the fibrosis thickness of the control group was 3.84 mm, which was significantly thicker than that of our study’s stent group (0.46 mm).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In addition, brosis in the stent group was signi cantly thicker than that in the control group. According to another previous animal study using PDO biliary stents 22 , the degree of brosis in the control group was more marked than that in the stent group at the duct-to-duct biliary anastomosis site. However, in that previous study, the brosis thickness of the control group was 3.84 mm, which was signi cantly thicker than that of our study's stent group (0.46 mm).…”
Section: Discussionmentioning
confidence: 82%
“…Using an in vitro bile flow phantom model, we evaluated degradation time, radial force changes, and morphologic changes of DBBS. Using an in vivo swine bile duct stricture model, we performed a DPOC examination and histopathologic evaluation to observe the biodegradation process and therapeutic effects of DBBS at regular intervals 1 2 3 .…”
mentioning
confidence: 99%